Formal and Informal Language Features in the Academic Writing of Fourth-Semester EFL Students - Angelica, Angelica; Sumarni, Sumarni; Rezeki, Yanti Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
Academic writing requires clarity, precision, and objectivity, which can be achieved through formal language. However, students often apply informal language in their actual practices. This descriptive qualitative research analyzed the dominant type of language features utilized by 23 fourth-semester students. It also analyzed the rhetorical purposes for which they utilized them. Additionally, this study explored students’ awareness of using formal language features and avoiding informal ones in their academic writing. Data were collected from argumentative essay assignments and a questionnaire. The findings indicate the predominantly utilized formal language features in their essays. These included precise wording (with lexical density greater than 61%), passive voice, and hedging. The informal language features predominantly applied were colloquial expressions, followed by two-word verbs, idiomatic expressions, and contractions. This study contributes to the existing literature on academic writing. It also provides information to improve academic writing courses and guides students toward more formal academic writing.